Impact of Green Certification on Customer Satisfaction, Mediated by Perceived Hotel Quality - Alhassan Fatawu; Lydia Adama; Stanley Cowther (Journal of Social Responsibility, Tourism and Hospitality, 2024)
This study investigates the impact of green certification on customer satisfaction, with a focus on the mediating role of perceived hotel quality. A quantitative research approach and correlational design were employed, surveying 256 respondents from hotels within the Tamale Metropolis. The findings reveal that green certification has a significant positive influence on both service quality and customer satisfaction, confirming that environmentally sustainable practices improve overall guest experiences. Moreover, the study highlights that service quality mediates the relationship between green certification and customer satisfaction, suggesting that hotels with green certification benefit from enhanced perceived quality, which in turn leads to higher guest satisfaction. Several challenges were identified that hinder the sustainability of green certification in hotels, including high implementation costs, lack of staff training, inconsistent government policies, and limited customer awareness and demand. These barriers suggest the need for strategic interventions, such as financial support, improved staff training programs, and enhanced customer engagement with sustainability efforts. The study concludes that while green certification plays a vital role in boosting service quality and customer satisfaction, addressing these challenges is critical for the long-term success and sustainability of green-certified hotels.